The Role of Traditional Balinese Music in the Formation of Social and Cultural Identity: A Systematic Literature - Dedy Iswanto; Ziqrurrahman Irsyad; Istiqlal (Journal of Music Science, Technology, and Industry, 2026)
Purpose: This study aims to examine the role of traditional Balinese music, particularly gamelan, in shaping the social and cultural identity of Balinese society amid the challenges of globalization, with a focus on the impact of ethnic tourism and innovations in gamelan composition. Method: Using a Systematic Literature Review (SLR) approach based on the PRISMA 2020 guidelines, this study analyzed 15 relevant articles selected from the Scopus and Web of Science databases. Result and Discussion: Key findings indicate that gamelan music plays a significant role in strengthening Balinese social identity, both in religious ceremonies and as a cultural symbol that preserves traditional values. However, ethnic tourism has a dual impact, preserving culture while risking the commodification of art, which diminishes the original meaning of traditional Balinese music. Implication: Innovations in gamelan composition are proven to be crucial for maintaining the cultural relevance of Balinese music without sacrificing its traditional essence. This study identified limitations in the methodology used, as well as challenges in applying the findings in real-world contexts, particularly regarding the influence of tourism. Recommendations for future research include the use of interdisciplinary methodologies and sustainable tourism policies to ensure the preservation of Balinese culture.